Bovine tuberculosis in youngstock cattle: A narrative review - Byrne, Andrew W.; Barrett, Damien; Breslin, Philip; Fanning, June; Casey, Miriam; Madden, Jamie M.; Lesellier, Sandrine; Gormley, Eamonn (Frontiers in Veterinary Science, 2022)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, remains a high-priority global pathogen of concern. The role of youngstock animals in the epidemiology of bTB has not been a focus of contemporary research. Here we have aimed to collate and summarise what is known about the susceptibility, diagnosis, transmission (infectiousness), and epidemiology to M. bovis in youngstock (up to 1-year of age). Youngstock are susceptible to M. bovis infection when exposed, with the capacity to develop typical bTB lesions. Calves can be exposed through similar routes as adults, via residual infection, contiguous neighbourhood spread, wildlife spillback infection, and the buying-in of infected but undetected cattle. Dairy systems may lead to greater exposure risk to calves relative to other production systems, for example, via pooled milk. Given their young age, calves tend to have shorter bTB at-risk exposure periods than older cohorts. The detection of bTB varies with age when using a wide range of ante-mortem diagnostics, also with post-mortem examination and confirmation (histological and bacteriological) of infection. When recorded as positive by ante-mortem test, youngstock appear to have the highest probabilities of any age cohort for confirmation of infection post-mortem. They also appear to have the lowest false negative bTB detection risk. In some countries, many calves are moved to other herds for rearing, potentially increasing inter-herd transmission risk. Mathematical models suggest that calves may also experience lower force of infection (the rate that susceptible animals become infected). There are few modelling studies investigating the role of calves in the spread and maintenance of infection across herd networks. One study found that calves, without operating testing and control measures, can help to maintain infection and lengthen the time to outbreak eradication. Policies to reduce testing for youngstock could lead to infected calves remaining undetected and increasing onwards transmission. Further studies are required to assess the risk associated with changes to testing policy for youngstock in terms of the impact for within-herd disease control, and how this may affect the transmission and persistence of infection across a network of linked herds.